SUPPORT FOR ETHNO-RELIGIOUS VIOLENCE IN INDONESIA - Tri Subagya (Masyarakat Indonesia, 2015)
This study focused on the relationship between ethno-religious identification and support for intergroup violence in Indonesia. It employed a cross-cultural comparative research design involving Muslim and Christian respondents from different ethnic groups in two research areas. One of these areas, Ambon, experiences frequent eruptions of inter-group violence, while the other, Yogyakarta, is relatively peaceful; while disputes have occurred occasionally, they have not led to massive intergroup violence. This research used a mixture of quantitative and qualitative approaches This study finds stronger identification with religion than with ethnicity. Muslims show greater ethno-religious identification than Christians. It also presents evidence for the proposition regarding religiocentrism in which a positive evaluation of the religious in-group is related to in-group identification and induces derogatory attitudes towards out-groups. The findings are also consistent with propositions concerning nationalistic attitudes which suggest that increased ethno-religious identification reduces nationalism.Keyword: ethnicity, religion, ethno-religious identification, support for violence, perceived group threat, religiocentrism, nationalism